Synthesis of a Geopolymer Binders Using Spent Fluid Catalytic Cracking (FCC) Catalyst - Ruiz G. (2019)
A synthesis of a geopolymer binder using spent fluid catalytic cracking (FCC) catalyst is evaluated in this research. Spent FCC catalyst is a solid waste product from the oil refining industry worldwide. It is composed mainly by aluminium and silicon oxides. The silica modulus (Ms), NaOH molar concentration, and liquid/solid (AS/FCC) weight ratio were studied as key factors of the mixture composition for the evaluation of the compressive strength and bulk density of geopolymers. Additional total ratios of SiO2/Al2O3, Na2O/SiO2, and H2O/total solids, which consider chemical composition of the final mixture, were studied. Results indicate that there is an optimum value for each Ms, NaOH molar concentration and AS/FCC that produces the maximum compressive strength. These values also match with the optimized total ratios of SiO2/Al2O3, N2O/SiO2 and H2O/total solids in the mixture, which can be considered as alternative control parameters for the formulation process. The bulk density is more related to AS/FCC value. A geopolymer binder with a compressive strength of 24.7 MPa after curing for one day at 65°C and six days at room temperature was produced using this spent FCC waste. © Published under licence by IOP Publishing Ltd.